Abdominal‐B regulates structure and development of the Harmonia axyridis cremaster. (21st July 2020) - Zhang, Yi; Wang, Xing‐Xing; Shen, Ling‐Feng; Feng, Zhu‐Jun; Zhang, Song‐Qi; Tian, Hong‐Gang; Feng, Yi; Liu, Tong‐Xian
Abstract: The ladybird Harmonia axyridis is an insect that exhibits pupal attachment to plants, which facilitates development and environmental adaptation. The cremaster is highly specialized for this behavior. However, the underlying molecular regulation of the cremaster remains unclear; therefore, we performed experiments to investigate the transcriptional regulation of cremaster development. First, we examined the morphological structure of the cremaster to reveal its function in pupal attachment of H. axyridis . Next, we analyzed the Hox gene Ha‐Abd‐B using RNA interference (RNAi) to determine its function in regulating cremaster formation; Ha‐Abd‐B up‐regulation promoted effective pupal attachment, whereas successful RNAi caused severe down‐regulation of this gene, and pupae were unable to attach. Furthermore, successful RNAi and subsequent Ha‐Abd‐B down‐regulation caused phenotypic changes in cremaster structure, including its complete disappearance from some individuals. Finally, we observed unique development of the cremaster and dynamic expression of Ha‐Abd‐B during pre‐pupal development; consequently, we hypothesized that there was specific pre‐pupal development of the cremaster. Overall, based on these results, the specialized cremasteric structure located on the posterior side of H. axyridis was determined to be a key organ for pupal attachment. Cremaster identification in H. axyridis is regulated by Ha‐Abd‐B and exhibits preferential development. Pupal attachment of H. axyridis reveals an environmental adaptation of this species; thus, this study and future molecular studies will help determine the role of Hox genes in regulation of insect attachment and further our understanding of the multiple functions of Hox genes.